The impact of integrated marketing communication on customer behavior - Daliborka Blazheska; Natasha Ristovska; Angela Milenkovska Klimoska (UTMS Journal of Economics, 2021)
The application of integrated marketing communications has become an imperative nowadays. Companies try to impose themselves on the market and win over customers and also keep them. Integrated marketing communications are a key element in the company's modern efforts to build long-term customer relationships. The company estimates which tools and forms of the promotional mix it will use before delivering adequate messages to its customers. In fact, integrated marketing communications are the answer to how companies can be competitive in their operations by establishing good communication relationships with customers in the long run. In this paper, special emphasis is placed on the research of how Macedonian companies are aware of the impact of integrated marketing communications on customer behavior. From the research we can see that it is necessary to approach the use of a larger number of communication tools, using a sophisticated coordination mechanism. IMC strives to cover all the communication tools of the company for the target audience to receive a consistent message that will influence customers behavior.
Keywords: M30; M13; 330; Integrated marketing communications; customers behavior; companies; competitive advantage